Biomechanical analysis on roundhouse kick in taekwondo - Li, Y.; Yan, F.; Zeng, Y.; Wang, G. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Taking a part of athletes of Taekwondo in Wuhan Institute of Physical Education as subjects, this study employed "Fighting Event-related Group Training Testing Machine" to get important athletes' data of roundhouse kick. In point of biomechanical view, it's easy to draw a conclusion that kick force (F) and kick velocity (V) were different about the front and back roundhouse kick when the suspended targets were at the angles of 90° and 110°. Therefore the purpose of this article was to draw its biomechanical characteristics and provide theoretic basis for teaching and training of Taekwondo.